Distinct methylation profile of mucinous ovarian carcinoma reveals susceptibility to proteasome inhibitors. Issue 2 (8th March 2018) - Liew, Phui‐Ly; Huang, Rui‐Lan; Weng, Yu‐Chun; Fang, Chia‐Lang; Hui‐Ming Huang, Tim; Lai, Hung‐Cheng
Abstract : Mucinous type of epithelial ovarian cancer (MuOC) is a unique subtype with a poor survival outcome in recurrent and advanced stages. The role of type‐specific epigenomics and its clinical significance remains uncertain. We analyzed the methylomic profiles of 6 benign mucinous adenomas, 24 MuOCs, 103 serous type of epithelial ovarian cancers (SeOCs) and 337 nonepithelial ovarian cancers. MuOC and SeOC exhibited distinct DNA methylation profiles comprising 101 genes, 81 of which exhibited low methylation in MuOC and were associated with the response to glucocorticoid, ATP hydrolysis‐coupled proton transport, proteolysis involved in the cellular protein catabolic process and ion transmembrane transport. Hierarchical clustering analysis showed that the profiles of MuOC were similar to colorectal adenocarcinoma and stomach adenocarcinoma. Genetic interaction network analysis of differentially methylated genes in MuOC showed a dominant network module is the proteasome subunit beta ( PSMB ) family. Combined functional module and methylation analysis identified PSMB8 as a candidate marker for MuOC. Immunohistochemical staining of PSMB8 used to validate in 94 samples of ovarian tumors (mucinous adenoma, MuOC or SeOC) and 62 samples of gastrointestinal cancer. PSMB8 was commonly expressed in MuOC and gastrointestinal cancer samples, predominantly as strong cytoplasmic and occasionally weak nuclei staining, but was not expressed in SeOC samples. Carfilzomib, a second‐generation proteasome inhibitor, suppressed MuOC cell growth in vitro . This study unveiled a mucinous‐type‐specific methylation profile and suggests the potential use of a proteasome inhibitor to treat MuOC. Abstract : What's new? Epigenetic changes such as DNA methylation play an important role in cancer development. In this study, the authors found that mucinous epithelial ovarian cancers (MuOC) display changes in methylation similar to those seen in colorectal and gastric cancers, especially in the proteasome system. They also found that a proteasome subunit called PSMB8 may provide a useful diagnostic marker for MuOC, and that proteasome inhibitors blocked the growth of MuOC cells. These results suggest that the proteasome system may offer a useful target for both diagnosis and treatment of MuOC.